TREATMENT OF DRUG THERAPY IN PATIENTS WITH ISCHEMIC HEART DISEASE - Kutlikova G. M. (Scholar Express Journals, 2024)
The development of recommendations based on the results of clinical trials, with a unified approach to treatment, modern drugs for the treatment of coronary artery disease, undoubtedly led to a significant improvement in the quality of life of patients and prognosis, however, the disease is still a poor predictor of drug therapy for coronary artery disease in order to achieve improvement quality of life and prognosis, slowing down the progression of the disease became possible thanks to the creation of a new drug nebivalol. The effective effect of nebivalol on the incidence of outcomes (death or hospitalization for coronary artery disease) was manifested in patients of different sex and age in the early stages of treatment and was maintained throughout the entire follow- up period.
Keywords: ischemic heart disease; lipid spectrum; sympathoadrenal system